Traditional Architects’ Accounts of the Processes of Rural and Country Housing Design and Construction (Case Study of Garmsar & Surrounding Townships) - Akbar Zargar; Mohsen Sartipipour; Seyed Hassan Miri; Hamed Sheikhtaheri (مسکن و محیط روستا)
Around one third of Iranian population live in rural housing. The physical characteristics of rural housing have been shaped by economic, social, cultural and environmental factors and in response to the ecological and livelihood needs. Architects and inhabitants play fundamental roles in the formation of rural housing. Therefore, their cooperation can influence creating desirable rural housings. Nowadays most rural houses of Iran, and in particular Garmsar County’s rural settlements, face a number of problems such as identity crisis, climate discomfort and environmental unsustainability. These problems have been exacerbated by a decrease in rural people participation in the process of design and construction of their houses. The aim of this research is to identify policies for increasing the efficiency and durability of rural housing as well as promoting active participation of people in the processes of housing design and construction. This research adopts a qualitative approach. It studies and analyses prevalent methods and techniques of traditional rural architecture in Garmsar County and explores those elements that shape the identity of vernacular architecture in this area. Collecting qualitative data relied on in-depth and semi-structured interviews with traditional architects of Garmsar rural districts as well as field observations. One of the approaches used in this study is action research. This approach requires a collaborative procedure between the researcher and rural inhabitants. This research highlights the importance of learning through practical experiences in developing local capacities, adaptable to the rural living condition. The analysis is based on a comparison between the characteristics and patterns of old and new rural housing architecture in Garmsar, Iran. Vernacular rural architecture of Gamsar area has elements and aspects that can be adopted in new architecture of rural housing. Not only can such adoption ensure the continuity across generations, but also it can revive the physical identity of the space and its responsiveness to the needs of villagers. This revitalization can be conducive to a sense of place attachment among rural inhabitants and restoring production-based rural life style, reducing energy consumption and enhancing climate comfort, increasing people participation and improving the quality of their lives. This study reveals that the reduction of villagers participation and a gradual disappearance of people-led housing processes in rural areas, has led the vernacular architecture methods and techniques being forgotten and also  the identity of rural life style and housing architecture in Garmsar county being damaged. In a mutual cooperation between dwellers and designers in the construction process, an accurate understanding of the needs and problems of inhabitants by local architects can reduce construction costs and increase the satisfaction of the villagers. Awareness is one of the essentials of participation. In today’s rural life, factors such as a lack of participatory experiences and awareness among the new generation compared to the previous ones regarding production-based housing and livelihood needs and the increasing similarity between rural and urban housing and living style have adversely affected rural people participation in housing. In order to promote people-centered rural development, it is necessary to prepare the ground for the presence of the clients – that is residents - alongside designers in the whole process of design and construction, in order to provide a better understanding of their living and livelihood spaces.